Mathematical models for the viscosity-temperature relationship of the lubricants containing nanoparticles and its applications to journal bearings. (1st January 2013) - Kalakada, Sreedhar Babu; Prabhakaran Nair, K.; Rajendrakumar, P.K.
In this paper, various mathematical models obtained for relationship between viscosity and temperature for the lubricants containing nanoparticles is presented. These models are used to predict the static performance characteristics of journal bearing operating under lubricants containing nanoparticles. The nanoparticles used for the present work are CuO, CeO2 and Al2 O3 . Viscosity models for the nanolubricants are developed with the available experimental data. These models are essential for the computation of performance characteristics of journal bearings. The modified Reynolds and energy equations are used to obtain pressure and temperature distribution across the lubricant film and these equations are solved by using the finite-element method and a direct iteration scheme. The static performance characteristics of journal bearing are computed for various values of eccentricity ratios and aspect ratios. The computed results show that addition of nanoparticles increase the viscosity of lubricants and in turn load capacity of journal bearing.